2009
DOI: 10.1016/s1734-1140(09)70111-2
|View full text |Cite
|
Sign up to set email alerts
|

Role of NF-κB in the pathogenesis of diabetes and its associated complications

Abstract: The nuclear factor-kappaB (NF-kappaB) family is comprised of DNA-binding protein factors that are required for the transcription of most proinflammatory molecules, including adhesion molecules, enzymes, cytokines, and chemokines. Studies performed in a variety of cell and animal based experimental systems suggest that NF-kappaB activation is a key event early in the pathobiology of diabetes. The purpose of this review is to summarize the current knowledge about the molecular biology of NF-kappaB and to review … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
195
0
4

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 260 publications
(206 citation statements)
references
References 67 publications
7
195
0
4
Order By: Relevance
“…It is generally accepted that many intracellular signal pathways participate in the LPS-induced activation of macrophages and resultant production of pro-inflammatory cytokines/ mediators, and that nuclear factor NF -κB and mitogenactivated protein kinase MAPK pathways play key roles. NF-κB is one of the most ubiquitous transcription factors and coordinates the expression of pro-inflammatory enzymes and cytokines, making it a popular target for the development of potent inhibitors as novel anti-infl ammatory drugs [21][22][23][24] . Given the role of NF-κB in modulating the expression of infl ammatory mediators, it is possible that the inhibitory effects of D-limonene involve the inhibition of the NF-κB signalling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…It is generally accepted that many intracellular signal pathways participate in the LPS-induced activation of macrophages and resultant production of pro-inflammatory cytokines/ mediators, and that nuclear factor NF -κB and mitogenactivated protein kinase MAPK pathways play key roles. NF-κB is one of the most ubiquitous transcription factors and coordinates the expression of pro-inflammatory enzymes and cytokines, making it a popular target for the development of potent inhibitors as novel anti-infl ammatory drugs [21][22][23][24] . Given the role of NF-κB in modulating the expression of infl ammatory mediators, it is possible that the inhibitory effects of D-limonene involve the inhibition of the NF-κB signalling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…21 NF-KB plays a role in these systems processing via positive regulatory factors by TNF-α, IL-6, and IL-1ß, 22 which indicates the close relationship between neurological disorders and NF-KB activity in the expression of proinflammatory cytokines. 9 Therefore, NF-KB can play a role in some processes including synaptic plasticity, synaptic transmission, learning, and memory. 23 In the present study, increase in the amount of expression of NF-KB gene in diabetic group is significant compared with the control group, which could be a reason for increased apoptosis observed in the hippocampus of the diabetic rats.…”
Section: Discussionmentioning
confidence: 99%
“…7 Nuclear factor kappa B (NF-KB) is a transcription factor that is involved in the cellular response to the stimulations like proinflammatory cytokines such as tumor necrosis factor alpha (TNF-α) and interleukins (IL). 9 Activation of NF-KB is an important event in the gradual reduction of beta cells during diabetes where preventing this process provides a protection for beta cells against apoptosis inducted by cytokine. 10 Several studies have reported that diabetes, as an inflammatory disease, increases the level of NF-KB in most of the tissues in the body.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…System inflamasi ini diaktifkan oleh NF-K melalui regulasi cyclooxygenase, lipooxygenase, cytokine, chemokine dan proses adesi molekul [4]. Pada keadaan diabetes, kegiatan NF-K akan memicu disfungsi sel beta pancreas sehingga terjadi apoptosis yang progresif pada sel tersebut [5].…”
Section: Pendahuluanunclassified